A shortcut to high-affinity Ga-68 and Cu-64 radiopharmaceuticals: one-pot click chemistry trimerisation on the TRAP platform1. Issue 24 (28th June 2015) - Baranyai, Zsolt; Reich, Dominik; Vágner, Adrienn; Weineisen, Martina; Tóth, Imre; Wester, Hans-Jürgen; Notni, Johannes
<x xml:space="preserve">Abstract</x> The kinetic inertness profile of Cu(ii) complexes of TRAP-conjugates enables simple Cu(ii) removal after click functionalisation and confirms their suitability for Cu-64-PET.